Public management and governance in Malaysia : transformations and trends - Siddiquee, Noore Alam. (Routledge/City University of Hong Kong Southeast Asian studies ;, 2013)
"The past two and a half decades have seen major transformations in public sector management and governance across the globe. This book examines the ways public sector management and governance in Malaysia has changed and is changing under contemporary reform models. Chapters are written by well-established scholars and academics with intimate knowledge in their respective fields, and provide a thorough and insightful analysis of the reform trends and developments on a range of topics. These include performance management, compensation reforms, public budgeting, accounting and reporting, privatisation and public-private partnership, e-government, managing ethics and accountability, local government and inter-governmental relations. While the book surveys the topics that are central to public sector management and governance, it also focuses on the nature of reforms and changes that were introduced, as well as the forces that have shaped their design and implementation process, and the initial impacts and results"--